Data Descriptor: Smart subsidies for catchment conservation in Malawi - Bell, Andrew Reid; Ward, Patrick S.; Mapemba, Lawrence; Nyirenda, Zephania; Msukwa, Wupe; Kenamu, Edwin (Nature Publishing Group, 2018)
Conservation agriculture (CA) is a management paradigm in which soil is covered outside of cropping seasons, minimally disturbed, and recharged with nitrogen-fixing legumes. Finding effective ways to encourage CA is a centuries-old problem playing out acutely today in Sub-Saharan Africa. To better understand this issue, we have collected data on rural livelihoods and CA adoption during a two-year intervention in southern Malawi. The intervention evaluated rates of CA adoption under two different structures of payment and three levels of monitoring. The dataset includes a baseline and endline survey covering 1,900 households, along with surveys conducted with participants opting into the intervention. Baseline and endline questions included modules on farm-level inputs and production at the plot-crop level; plot characteristics; household composition and assets; savings, loans, and other sources of income; neighborhood characteristics; and perceptions regarding CA. Registration questionnaires in the intervention included detailed assessments of recent production in plots being registered to the intervention, and basic information for all other plots; and basic information on household structure and assets.